A29 Physical Activity through Sustainable Transport Approaches (PASTA) – a pan-European web-based survey on determinants of active travel behaviour using an opportunistic sampling approach. Issue 2 (June 2015) - Götschi, Thomas; Standaert, Arnout; Eriksson, Ulf; Dons, Evi; Int Panis, Luc; Kahlmeier, Sonja; de Nazelle, Audrey; Anaya, Esther; Nieuwenhuijsen, Mark; Rojas-Rueda, David; Brand, Christian; Gerike, Regine
Abstract: Background: Active travel (AT), i.e. walking and bicycling, is a promising approach to increase physical activity (PA). Research on determinants of AT is growing and health impact models (HIM) demonstrate benefits of AT. However, substantial research gaps remain. The PASTA project (www.pastaproject.eu) is a broad study of determinants of AT including safety, measures to promote AT, and HIM. It integrates planning, travel behavior and health research, policy and practice. Methods: PASTA is a 4-year project (2013-2017) involving 7 European cities (Antwerp, Barcelona, Oerebro, Rome, Vienna, Zurich). A longitudinal web-based survey which consists of a substantial baseline questionnaire (on average 120 data points) and bi-weekly short (14) and a monthly long (21) follow-ups was launched in November 2014. Survey contents were defined based on a comprehensive conceptual framework which combines a rationalist mode choice, a socio-geographical and a socio-psychological perspective. In addition it includes PA (adapted GPAQ separating walking and cycling) and health related items. Participants experiencing crashes fill out an additional questionnaire. Participants are recruited opportunistically on a rolling basis (target sample size: 2000 per city) and sample characteristics are monitored on an ongoing basis. Parts of the sample will be recruited randomly. Subsamples are used to evaluate AT measures (pre-post) and to collect objective data as part of add-on modules (GPS tracking, accelerometry, air pollution exposure). Results: To date, 1802 participants have been recruited, mainly in Antwerp (1168) and Barcelona (300). Preliminary data suggests drop-out rates of 20-25% for short and approximately 50% for long follow-up questionnaires. Questionnaire completion rate (80% of average data input) are above 80% for baseline, above 90% for short and 85% for long follow-up questionnaire. Users report on average 1.4 trips per day in travel diary. 54% of participants are women. 65% report walking and 12% report biking daily or almost daily. Conclusions: The PASTA survey promises to provide insights on variation in travel and physical activity behavior over time, which is important for HIM and various other issues in AT research. Survey implementation has passed a first test of practicality and monitoring features to optimize sample distribution and recruitment strategies are in place. Early results are promising with regards to representative sample distribution and how extraordinary user burden of frequent follow-ups is handled. By July we will be able to report more reliable participation statistics including additional cities and participant attributes, as well as comparisons with the target populations.